2020
DOI: 10.1097/md.0000000000022360
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture for post-stroke dysphagia

Abstract: Background: Post-stroke dysphagia (PSD) requires effective treatment as it may cause aspiration pneumonia, dehydration, or malnutritution, which can increase the length of hospital stay as well as mortality. In the field of stroke, electroacupuncture (EA) has been widely used, and a number of clinical research papers have been published regarding its effects. This systematic review aims to evaluate the effectiveness of EA for the treatment of PSD. Methods: Randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…Dysphagia can affect food intake and nutrient absorption and can also lead to aspiration pneumonia after food inhalation into trachea, which can be life-threatening in severe cases. 2 Though dysphagia after stroke is very common, its treatments and efficacy evaluation methods are very limited now. 11 At present, swallowing training is the most commonly used intervention method for dysphagia, which can help patients know swallowing movements and gradually restore swallowing function through training swallowing-related muscles.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Dysphagia can affect food intake and nutrient absorption and can also lead to aspiration pneumonia after food inhalation into trachea, which can be life-threatening in severe cases. 2 Though dysphagia after stroke is very common, its treatments and efficacy evaluation methods are very limited now. 11 At present, swallowing training is the most commonly used intervention method for dysphagia, which can help patients know swallowing movements and gradually restore swallowing function through training swallowing-related muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Research has showed that > 50% of stroke patients experience dysphagia of varying degrees. 1,2 Dysphagia leads to coughing or accidental swallowing and increases the risks of malnutrition and aspiration pneumonia. It also extends hospital stay and causes extra charges, seriously compromising the life qualities and prognoses of stroke patients, even increasing mortality.…”
mentioning
confidence: 99%
See 3 more Smart Citations